"You kind of want to fix it don't you?" Exploring general practice trainees' experiences of managing patients with medically unexplained symptoms. Issue 1 (December 2016) - Howman, Mary; Walters, Kate; Rosenthal, Joe; Ajjawi, Rola; Buszewicz, Marta
Abstract Background Much of a General Practitioner's (GP) workload consists of managing patients with medically unexplained symptoms (MUS). GP trainees are often taking responsibility for looking after people with MUS for the first time and so are well placed to reflect on this and the preparation they have had for it; their views have not been documented in detail in the literature. This study aimed to explore GP trainees' clinical and educational experiences of managing people presenting with MUS. Method A mixed methods approach was adopted. All trainees from four London GP vocational training schemes were invited to take part in a questionnaire and in-depth semi-structured interviews. The questionnaire explored educational and clinical experiences and attitudes towards MUS using Likert scales and free text responses. The interviews explored the origins of these views and experiences in more detail and documented ideas about optimising training about MUS. Interviews were analysed using the framework analysis approach. Results Eighty questionnaires out of 120 (67 %) were returned and a purposive sample of 15 trainees interviewed. Results suggested most trainees struggled to manage the uncertainty inherent in MUS consultations, feeling they often over-investigated or referred for their own reassurance. They described difficulty in broaching possible psychological aspects and/or providing appropriate explanations to patients for their symptoms. They thought that more preparation was needed throughout their training. Some had more positive experiences and found such consultations rewarding, usually after several consultations and developing a relationship with the patient. Conclusion Managing MUS is a common problem for GP trainees and results in a disproportionate amount of anxiety, frustration and uncertainty. Their training needs to better reflect their clinical experience to prepare them for managing such scenarios, which should also improve patient care.